Students’ Meaning-Making of REBT Counseling in Reducing Aggression - Dinda Rachma Aulia Agustine; Desi Maulia; Ellya Rakhmawati (Universitas Ahmad Dahlan, 2026)
This study aimed to explore students’ meaning-making and the effectiveness of Rational Emotive Behavior Therapy (REBT) counseling in reducing aggressive behavior among junior high school students. A qualitative approach with an Interpretative Phenomenological Analysis (IPA) design was employed to capture participants’ subjective experiences during the counseling process. Participants were purposively selected based on sociometric results indicating high levels of aggression and social rejection. Data were collected through semi-structured in-depth interviews, observation, and documentation. The findings revealed three main themes: aggression as emotional expression and sensation-seeking behavior, irrational beliefs underlying aggressive actions, and increased self-awareness alongside cognitive change following REBT counseling. Initially, participants perceived aggression as a normal way to express emotions, reinforced by self-justifying irrational beliefs. After the intervention, participants demonstrated cognitive restructuring, enhanced self-awareness, and more adaptive emotional responses. These findings suggest that reducing aggression involves both observable behavioral changes and deeper cognitive transformation. REBT appears to be an effective and meaningful approach for promoting rational thinking and emotional regulation among adolescents.